Lateral dispersion of dye and drifters in the center of a very large lake. (16th August 2019) - Choi, Jun; Troy, Cary; Hawley, Nathan; McCormick, Michael; Wells, Mathew
Abstract: To better understand lateral dispersion of buoyant and nonbuoyant pollutants within the surface waters of large lakes, two lateral dispersion experiments were carried out in Lake Michigan during the stratified period: (1) a dye tracking experiment lasting 1 d; and (2) a drifter tracking experiment lasting 24 d. Both the dye patch and drifters were surface‐released at the center of Lake Michigan's southern basin. Near‐surface shear induced by near‐inertial Poincaré waves partially explains elevated dye dispersion rates (1.5–4.2 m 2 s −1 ). During the largely windless first 5 d of the drifter release, the drifters exhibited nearly scale‐independent dispersion ( K  ∼  L 0.2 ), with an average dispersion coefficient of 0.14 m 2 s −1 . Scale‐dependent drifter dispersion ensued after 5 d, with K  ∼  L 1.09 and corresponding dispersion coefficients of 0.3–2.0 m 2 s −1 for length scales L = 1500–8000 m. The largest drifter dispersion rates were found to be associated with lateral shear‐induced spreading along a thermal front. Comparisons with other systems show a wide range of spreading rates for large lakes, and larger rates in both the ocean and the Gulf of Mexico, which may be caused by the relative absence of submesoscale processes in offshore Lake Michigan.